2013
DOI: 10.1038/modpathol.2012.235
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability and the effect of education in the histopathological diagnosis of differentiated vulvar intraepithelial neoplasia

Abstract: No published data concerning intraobserver and interobserver variability in the histopathological diagnosis of differentiated vulvar intraepithelial neoplasia (DVIN) are available, although it is widely accepted to be a subtle and difficult histopathological diagnosis. In this study, the reproducibility of the histopathological diagnosis of DVIN is evaluated. Furthermore, we investigated the possible improvement of the reproducibility after providing guidelines with histological characteristics and tried to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 23 publications
3
46
0
1
Order By: Relevance
“…Two possible explanations for the low incidence of dVINs are (1) that it is a transient intraepithelial lesion that rapidly progresses to invasive carcinoma or (2) that it is an underdiagnosed lesion because of its difficult clinical and histological recognition. 25 The latter is further supported by a recent study on the basis of a careful review of previously reported histological specimens, where dVIN was found in 42% of lesions previously diagnosed with VLS, which progressed to vulvar SCC. 26 Rapid progression to neoplasia or its underdiagnosis could also explain why dVIN accounts for only 2% to 10% of all reported VIN in the literature.…”
Section: Discussionsupporting
confidence: 53%
“…Two possible explanations for the low incidence of dVINs are (1) that it is a transient intraepithelial lesion that rapidly progresses to invasive carcinoma or (2) that it is an underdiagnosed lesion because of its difficult clinical and histological recognition. 25 The latter is further supported by a recent study on the basis of a careful review of previously reported histological specimens, where dVIN was found in 42% of lesions previously diagnosed with VLS, which progressed to vulvar SCC. 26 Rapid progression to neoplasia or its underdiagnosis could also explain why dVIN accounts for only 2% to 10% of all reported VIN in the literature.…”
Section: Discussionsupporting
confidence: 53%
“…In a recent study on the reproducibility of diagnosis of dVIN, van den Einden et al 13 showed poor reproducibility/high interobserver variation. They identified 5 key histopathologic features of dVIN: (1) atypical basal mitotic figures, (2) basal atypia, (3) dyskeratosis, (4) prominent nucleoli, and (5) elongation and anastomosis of rete ridges.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, most cases of dVIN are diagnosed in association with invasive SCC, and isolated dVIN, without invasion, is uncommonly recognized by pathologists. 12,13 Mutations in TP53 are a hallmark of HPV-independent vulvar SCC. [14][15][16] It is now appreciated that mutant TP53 can show 1 of 2 patterns of expression on immunohistochemical (IHC) staining.…”
mentioning
confidence: 99%
“…Although the majority of vulvar SCC is not HPV associated, dVIN accounts for only 2e10% of all reported VIN. The possible explanations for dVIN's low prevalence are that it is a transient lesion that rapidly progresses to invasive carcinoma and/or it is an underdiagnosed and underreported lesion [17,18].…”
Section: Vulvar Oncogenesismentioning
confidence: 98%